Relationship of Balloon Size in Pulmonary Valvuloplasty Outcome - Baqir Maqbool, Muhammad Younas, Tauseef Asma Chaudhry, Rubina Tousif, Farhan Ul Haq, Shoaib Saleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the relation between balloon size and outcome of patients undergoing pulmonary valvuloplasty. Study Design: A quasi-experimental study. Place and Duration: Pediatric Cardiology Department of Chaudhary Pervaiz Elahi Institute of Cardiology, Multan, Pakistan from January 2021 to June 2022. Methodology: Children of both genders aged less than 15 years having severe pulmonary stenosis and who underwent pulmonary valvuloplasty during the study period were analyzed. After 24 hours post procedure, echocardiography was done to see echo gradient across pulmonary valve, tricuspid regurgitation, pulmonary regurgitation, right ventricular dysfunction or pericardial effusion. Procedure was considered successful if the residual gradient across pulmonary valve was < 40 mmHg, pulmonary regurgitation < moderate and patients had no major complications. Results: In a total of 75 children, 42 (56.3%) were male. The mean age was 6.24 ± 4.81 years. Cyanosis was observed in 10 (13.3%) children while there was right ventricular dysfunction in 6 (8.0%) children. The pulmonary valvuloplasty procedure was successful in 53 (70.6%) cases while in remaining 22 (29.4%) cases, the procedure was partially successful because of infundibular obstruction. We observed that the degree of pulmonary regurgitation was greater when annulus- balloon ratio was 1.3 or more than that (p<0.0001). Practical Implications: Large balloons do not impart advantages beyond that produced by balloons between 1.2-1.4 times of the annular size but further research is required to ascertain these findings Conclusion: Signification relation exists regarding balloon size and outcome of children undergoing pulmonary valvuloplasty as the degree of pulmonary regurgitation was greater when annulus- balloon ratio was 1.3 or more. Keywords: Cyanosis, pulmonary regurgitation, pulmonary valvuloplasty, right ventricular dysfunction.